Engraftment of rare, pathogenic donor hematopoietic mutations in unrelated hematopoietic stem cell transplantation - Wong, Wing Hing (Sci Transl Med, 2020)
Clonal hematopoiesis is associated with various age-related morbidities. Error-corrected sequencing (ECS) of human blood samples, with a limit of detection of ≥0.0001, has demonstrated that nearly every healthy individual >50 years old harbors rare hematopoietic clones below the detection limit of standard high-throughput sequencing. If these rare mutations confer survival or proliferation advantages, then the clone(s) could expand after a selective pressure such as chemotherapy, radiotherapy, or chronic immunosuppression. Given these observations and the lack of quantitative data regarding clonal hematopoiesis in adolescents and young adults, who are more likely to serve as unrelated hematopoietic stem cell donors, we completed this pilot study to determine whether younger adults harbored hematopoietic clones with pathogenic mutations, how often those clones were transferred to recipients, and what happened to these clones over time after transplantation. We performed ECS on 125 blood and marrow samples from 25 matched unrelated donors and recipients. Clonal mutations, with a median variant allele frequency of 0.00247, were found in 11 donors (44%; median, 36 years old). Of the mutated clones, 84.2% of mutations were predicted to be molecularly pathogenic and 100% engrafted in recipients. Recipients also demonstrated de novo clonal expansion within the first 100 days after hematopoietic stem cell transplant (HSCT). Given this pilot demonstration that rare, pathogenic clonal mutations are far more prevalent in younger adults than previously appreciated, and they engraft in recipients and persist over time, larger studies with longer follow-up are necessary to correlate clonal engraftment with post-HSCT morbidity.